IMPLEMENTASI MANAJEMEN PESERTA DIDIK DALAM MENINGKATKAN KUALITAS LAYANAN PENDIDIKAN DI SEKOLAH - Ilham Mayudho (Universitas Pendidikan Indonesia, 2022)
This study has the aim of providing a description of the implementation of a student management activity in providing a quality service in the realm of education. In conducting this research there is a research method used, namely the literature study method, because in the research all the data reviewed and collected for research materials come from journals or other reference sources that support online. This approach with the literature method can also be used to provide knowledge related to the subject matter. The collected data were analyzed or studied using descriptive analysis method. procedures for improving services to students in an educational institution or what can be called a school through the implementation of student manage-ment with the aim of improving the quality of education which includes student arrangements, student planning, student development, student transfers, evaluation of activities/ outcomes learn students.